PENGARUH SIMULASI TINDAKAN RESUSITASI JANTUNG PARU (RJP) TERHADAP TINGKAT MOTIVASI SISWA MENOLONG KORBAN HENTI JANTUNG DI SMA NEGERI 1 TELAGA - Pipin Yunus; Haslinda Damansyah (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Cardiac arrest is one of the emergency conditions that can be life-threatening. The objective of this study is to investigate the effect of Pulmonary Resuscitation Action Simulation (CPR) on Motivation of Students in Helping Victims of Cardiac Arrest in SMAN 1 Telaga. The sample was 76 respondents taken by using purposive sampling techniques. The design is quasy experiment with one group pre-post design and using questionnaire sheets to obtain data from respondents. The results of the study obtained a P-value of 0.00 (<= 0.05). It can be concluded that there is a significant influence of CPR action simulations on the level of motivation in helping victims of cardiac arrest in SMAN 1 Telaga. It suggests that the school especially students can utilize the experience and knowledge gained from simulation activities in order to increase motivation to help victims of cardiac arrest. Furthermore, it is possible to examine other factors that can increase motivation levels that were not discussed in this study